ESTIMATED PULSE WAVE VELOCITY (EPWV) DISTRIBUTION IN A COHORT STUDY – EH-UH STUDY (CROATIAN SCIENTIFIC FOUNDATION). (April 2021) - Bosnjak, Vito; Blagus, Luka; Frkanec, Stjepan; Katic, Luka; Domislovic, Viktor; Matasin, Marija; Glavic, Mihaela Marinovic; Kos, Jelena; Vrkic, Tajana Zeljkovic; Pecin, Ivan; Jelakovic, Ana; Premuzic, Vedran; et al.
Abstract : Objective: Carotid-femoral pulse wave velocity (cfPWV) was recommended by guidelines as a biomarker of arterial stiffness and an independent predictor of future cardiovascular (CV) events. However, due to practical and logistic reasons it was not become a routine in clinical work. Recently, it was shown that estimated PWV (ePWV) which is much more convenient for everyday work correlates excellent with cfPWV and had predictive role in hypertensive patients with various degrees of CV risk. Our aim was to determine the distribution of ePWV values in general Croatian population. Design and method: In a stratified random sample of 1087 subjects from the general Croatian adult population which was enrolled in a nationwide survey (EH-UH 1) from 2000–2005 analyses on ePWV were done and subjects were followed-up for 17 years. ePWV was calculated from age and mean BP (MBP): ePWV = 9.587 - 0.402 × age + 4.560 × 10-3 × age2 - 2.621 × 10-5 × age2 × MBP + 3.176 × 10-3 × age × MBP - 1.832 × 10-2 × MBP. MBP = diastolic BP (DBP) + 0.4(SBP - DBP). Results: Mean values of ePWV according to the age and BP categories are shown in Figure 1. Distribution of PWV according to the age category in the normal values European population (European Heart Journal 2010; 31: 2338) and ePWV in general Croatian population are presented in Table 1. Concordance between cfPWV and ePWV was found in younger subjects with less stiffed arteries. Discrepancies between cfPWV and ePWV increased with levels of cfPWV Figure. No caption available. Conclusions: According to our knowledge this is the first study presenting the distribution of ePWV by age category in a population-based survey. Observed differences between cfPWV and ePWV in older subjects could be explained with differences between groups (normal population vs. general population) but also by the fact that our participants were not classified according to levels of BP what is in line with the results of other authors (J of Hypertension 2016, 34:1279)